Intelligent data engineering and automated learning - IDEAL 2015 : 16th International Conference, Wrocław, Poland, October 14-16, 2015 : proceedings /: 16th International Conference, Wrocław, Poland, October 14-16, 2015 : proceedings. (2015) - Unknown
No abstract available